Population distribution of plant-parasitic nematodes of bananas in Peninsular Malaysia - Sayed Abdul Rahman, S.A.; Mohd Zain, S.N.; Bilal Mat, M.Z.; Sidam, A.K.; Othman, R.Y.; Mohamed, Z. (Universiti Kebangsaan Malaysia, 2014)
A nematode population distribution survey was conducted in banana plantations/farms in Peninsular Malaysia from June 2004 to January 2006. This study highlights differences obtained from the survey compared with previously published reports in terms of species prevalence in banana plantations. As opposed to the widely reported prevalence of Radopholus similis (Cobb 1893) Thorne, 1949, on banana plants worldwide, Rotylenchulus reniformis Linford and Oliveira, 1940, was found to be the most common nematode species in the isolated soil samples (Prominence Value = 824.28; n=63) while Meloidogyne incognita (Kofoid & White 1919) Chitwood, 1949, was predominant in the isolated root samples (Prominence Value = 449.77; n=57) in Peninsular Malaysia. Besides, contradicting previous reports, M. incognita was found to dominate Cavendish plantation areas in this region instead of R. similis. Inter-species interaction resulting in species predominance and co-dominance in banana rhizosphere was also observed in this study.